Phytosphingosine, sphingosine and dihydrosphingosine ceramides in model skin lipid membranes: permeability and biophysics - Školová, Barbora; Kováčik, Andrej; Tesař, Ondřej; Opálka, Lukáš; Vávrová, Kateřina (Biochimica et biophysica acta. Biomembranes, 2017)
Ceramides based on phytosphingosine, sphingosine and dihydrosphingosine are essential constituents of the skin lipid barrier that protects the body from excessive water loss. The roles of the individual ceramide subclasses in regulating skin permeability and the reasons for C4-hydroxylation of these sphingolipids are not completely understood. We investigated the chain length-dependent effects of dihydroceramides, sphingosine ceramides (with C4-unsaturation) and phytoceramides (with C4-hydroxyl) on the permeability, lipid organization and thermotropic behavior of model stratum corneum lipid membranes composed of ceramide/lignoceric acid/cholesterol/cholesteryl sulfate. Phytoceramides with very long C24 acyl chains increased the permeability of the model lipid membranes compared to dihydroceramides or sphingosine ceramides with the same chain lengths. Either unsaturation or C4-hydroxylation of dihydroceramides induced chain length-dependent increases in membrane permeability. Infrared spectroscopy showed that C4-hydroxylation of the sphingoid base decreased the relative ratio of orthorhombic chain packing in the membrane and lowered the miscibility of C24 phytoceramide with lignoceric acid. The phase separation in phytoceramide membranes was confirmed by X-ray diffraction. In contrast, phytoceramides formed strong hydrogen bonds and highly thermostable domains. Thus, the large heterogeneity in ceramide structures and in their aggregation mechanisms may confer resistance towards the heterogeneous external stressors that are constantly faced by the skin barrier.
Keywords: vodíková vazba; X-ray powder diffraction; Stratum corneum; Skin barrier; biofyzika; Fourier-transform infrared spectroscopy; kůže; permeabilita buněčné membrány; hydroxylace; Ceramides; sfingosin; Hydroxylation; Sphingosine; Ceramide; Cell Membrane Permeability; ceramidy; Hydrogen Bonding; Biophysics; Skin; Model lipid membrane